Efficacy of Environmental DNA to Detect and Quantify Brook Trout Populations in Headwater Streams of the Adirondack Mountains, New York. Issue 1 (2nd January 2017) - Baldigo, Barry P.; Sporn, Lee Ann; George, Scott D.; Ball, Jacob A.
Abstract: Environmental DNA (eDNA) analysis is rapidly evolving as a tool for monitoring the distributions of aquatic species. Detection of species' populations in streams may be challenging because the persistence time for intact DNA fragments is unknown and because eDNA is diluted and dispersed by dynamic hydrological processes. During 2015, the DNA of Brook Trout Salvelinus fontinalis was analyzed from water samples collected at 40 streams across the Adirondack region of upstate New York, where Brook Trout populations were recently quantified. Study objectives were to evaluate different sampling methods and the ability of eDNA to accurately predict the presence and abundance of resident Brook Trout populations. Results from three-pass electrofishing surveys indicated that Brook Trout were absent from 10 sites and were present in low (<100 fish/0.1 ha), moderate (100–300 fish/0.1 ha), and high (>300 fish/0.1 ha) densities at 9, 11, and 10 sites, respectively. The eDNA results correctly predicted the presence and confirmed the absence of Brook Trout at 85.0–92.5% of the study sites; eDNA also explained 44% of the variability in Brook Trout population density and 24% of the variability in biomass. These findings indicate that eDNA surveys will enable researchers to effectively characterize the presence and abundance of Brook Trout and other species' populations in headwater streams across the Adirondack region and elsewhere. Received April 15, 2016; accepted September 26, 2016